The Management of Pediatric Oncology Inpatients With Oral Mucositis. Issue 8 (November 2019) - Hurrell, Lloyd; Burgoyne, Laura; Logan, Richard; Revesz, Tamas; Gue, Sam
Abstract : The purpose of the study was to investigate the management of chemotherapy-induced oral mucositis (OM) in pediatric patients. A total of 68 separate episodes of OM were assessed in 47 children who had received chemotherapy. The severity of the child's OM was assessed using 2 scales, and relevant clinical information was collected. The mean onset time of OM was 8.4 days (±4.0), with a median duration of 7.0 days (4.0, 10.5), with median admission of 7.0 days (4.5, 13.5). The overall adherence to an oral health protocol was 59%, which decreased with more severe OM. A third of patients used chlorhexidine mouthwash only, which was used in preference in cases of severe OM. Almost all patients had some systemic analgesia administered, with a significant increase in patient-controlled analgesia/nurse-controlled analgesia and intravenous ketamine in severe cases. Various types of prophylaxis/treatment of secondary infections and supportive care were associated with the severity of OM. The management of OM in children is important to limit its burden. An oral care protocol was recommended. Chlorhexidine mouthwash can maintain some form of oral care when brushing becomes too uncomfortable in severe OM. Pain management is important for the management of OM, and its intensity increases with increasing severity of OM.